Resonances. On a digital touch in Invisible, dance that explodes the senses and the notion of diaphanous in Aristotle. - Muñoz Carneiro, Sofía (Meridional. Revista Chilena de Estudios Latinoamericanos, 2019)
Based on the Chilean performance of contemporary dance, Invisible, danza que explota los sentidos (dance that explodes the senses) the article examines the experience of touching that the performance presents, where the tangible acquires an audible dimension through the use of digital devices for sound expansion. In this regard, a nocturnal character of the experience of touching will be explored, regarding its transformation into a new diaphanous, following Aristotle and the reading proposed by Rodrigo Zúñiga concerning the image-pixel. This whole movement is proposed as a diaphanous touch in dance, which in turn would lead to a new sensibility that would transform both the medium, as well as the bodies and corporalities in dance, regarding the interaction with the interface. Finally, this new sensibility of touching will be approached as a multi-sensory experience that can be understood as resonances of the invisible, mainly following the notions of resonance of Gilles Deleuze related to painting and that of Francisca Morand regarding Invisible